2010
DOI: 10.3923/ijar.2011.67.74
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impacts of Climate Change on the Rice Production in Malaysia

Abstract: This study attempts to estimate the potential impacts of climate change on the rice production in Malaysia. The crop model ORYZA2000 was used to simulate rice yield of MR 219 variety in eight granary areas of Malaysia from 1999-2007. The model predicted a reduction in rice yield of 0.36 t ha-1 under the scenario of an increase in temperature by 2°C and at the current CO 2 level of 383 ppm. With the reduction in rice yield, the economic loss to the Malaysian rice industry was estimated at RM162.531 million per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…Recently, the International Food Policy Research Institute (IFPRI) reported that climate change could reduce the paddy yield by 10 to 15%, which can result in a rise in market price by 32 to 37% [55,56]. Using historic data from 1999 to 2007, the ORYZA 2000 model predicted for Malaysia that a 2 • C temperature increase could reduce paddy yields by 0.36 t ha −1 , which would result in a huge economic loss [57]. Matthews et al, simulated the impact of increased atmospheric carbon dioxide on the productivity of rice in various parts of Asia and found that on average the yields will go down by 4% [58].…”
Section: Paddymentioning
confidence: 99%
“…Recently, the International Food Policy Research Institute (IFPRI) reported that climate change could reduce the paddy yield by 10 to 15%, which can result in a rise in market price by 32 to 37% [55,56]. Using historic data from 1999 to 2007, the ORYZA 2000 model predicted for Malaysia that a 2 • C temperature increase could reduce paddy yields by 0.36 t ha −1 , which would result in a huge economic loss [57]. Matthews et al, simulated the impact of increased atmospheric carbon dioxide on the productivity of rice in various parts of Asia and found that on average the yields will go down by 4% [58].…”
Section: Paddymentioning
confidence: 99%
“…Global climate change, however, has generated serious threats to achieving sustainable growth in rice production (Adams et al 1998;Wassmann and Dobermann 2007;IFPRI International Food Policy Research Institute 2010;Vaghefi et al 2011). Rice productivity and sustainability are already threatened by several biotic and abiotic stresses, and the effects of these stresses can be further aggravated by dramatic changes in global climate.…”
Section: Introductionmentioning
confidence: 98%
“…According to the reports of the International Panel on Climate Change (IPCC) in 2007 and the Food and Agriculture Organization of the United Nations (FAO) in 2008, humid tropical zones will suffer negative impacts of the climate change, which definitely affects the way of life and food production. Various studies have been conducted to measure the effects of climate change impacts on net farm revenue such as integration of the Environment Policy Integrated Climate (EPIC) model and International Food Policy and Agricultural Simulation (IFPSIM) model (Wu et al, 2007), ORYZA 2000 (Vaghefi et al, 2011), Global circulation model (GCM) (Tumbo et al, 2010), Ricardian model (Fleischer et al, 2007;Ajetomobi, 2010;Thapa and Joshi, 2010;Mendelsohn, 2014), Statistical approaches were used to analyze the relationships between observed yield and climate (Chen et al, 2013;Huang et al, 2013;Wang et al, 2014). Mostly, their outcome found that rice production will decline with increase in temperature and decrease in precipitation, with decrease the net revenue per hectare, especially in dry land and non-irrigated areas.…”
Section: Introductionmentioning
confidence: 99%